How America Became Capitalist Imperial Expansion and the Conquest of the West - Parisot, James (Pluto Press, 2019)
In an age of political and economic uncertainty, from the Great Recession to the election of Donald Trump, it is essential to understand the ways capitalism and imperialism are central to the American way of life.The story told in this book brings together a new interpretation of American history beyond mainstream perspectives to chart the ways in which white-settler colonialism pushed expansion on the western frontier of empire, and locates the history through which empire gradually took on a capitalist form.It follows the pathway of expansion from the making of an Atlantic world market through the creation of white colonies in New England and Virginia. From here the book charts the growth of empire across the north and south, highlighting the gendered dynamics of empire-building, and culminates in a discussion of the Civil War and the consolidation of over two centuries of capitalist development explaining how a society with capitalism became a capitalist society.